2020
DOI: 10.18805/lr-532
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Super Absorbent Polymers and Gibberellin on Germination and Growth of alfalfa

Abstract: For proven effects of eco-friendly super absorbent polymer and gibberellin on germination and growth of alfalfa, taking the germination and growth test in the artificial climate box by adding the different amount of super absorbent polymer and gibberellin. Observed the germination potential, germination rate, shoot length, root length, fresh weight and dry weight, under the different experiment conditions. The test showed that the super absorbent polymer had a promoting effect on alfalfa. The property of slowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Some studies have shown benefits to the germination of different species by applying SAP (SU et al, 2017;CASSOL et al, 2020;ZHANG et al, 2020;JANG et al, 2021). Yonezawa et al (2017) verified a 20% increase in okra (Abelmoschus esculentus) germination with a SAP dose of 0.3%.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown benefits to the germination of different species by applying SAP (SU et al, 2017;CASSOL et al, 2020;ZHANG et al, 2020;JANG et al, 2021). Yonezawa et al (2017) verified a 20% increase in okra (Abelmoschus esculentus) germination with a SAP dose of 0.3%.…”
Section: Discussionmentioning
confidence: 99%